2017
DOI: 10.1155/2017/6345810
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Types of Metallogenic Fluids in the Ultra-Large Huize Pb–Zn Deposit, SW China

Abstract: This work investigates the ultra-large Huize Pb-Zn deposit, based on the results of preceding studies and detailed field geological surveys. The existing findings were reorganized and reinterpreted and supplemented with C-H-O isotopic measurements, which resulted in the identification of two different metallogenic fluids: a high temperature, low salinity, and acidic Fluid A, which originates from deep-seated fluids and is enriched in lighter C and O isotopes (−3‰ < 13 C‰ < −4‰; 10‰ < 18 O‰ < 17‰; −92‰ < D‰ < −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This is an indication that the ore-forming fluids were related to water/rock (W/R) interaction between the mantle and/or metamorphic fluids and carbonates. The values obtained from this study are consistent with previous data of host rock and miarolitic calcites (Huang et al, 2003;Zhang et al, 2005b;Han et al, 2007;Zhang et al, 2017) but different from the primary ore calcites. The correlation between δ 1 3…”
Section: Insights From C-o Isotopessupporting
confidence: 92%
See 2 more Smart Citations
“…This is an indication that the ore-forming fluids were related to water/rock (W/R) interaction between the mantle and/or metamorphic fluids and carbonates. The values obtained from this study are consistent with previous data of host rock and miarolitic calcites (Huang et al, 2003;Zhang et al, 2005b;Han et al, 2007;Zhang et al, 2017) but different from the primary ore calcites. The correlation between δ 1 3…”
Section: Insights From C-o Isotopessupporting
confidence: 92%
“…values (+19.24 to 26.83‰, average of 13.28‰) of syn-ore calcite extracts from the Qilinchang deposit are significantly greater than that of the mantle-derived rocks (+6.0 to +10.0‰; Taylor et al, 1967), but most values are analogous to the marine carbonate rocks (+20.0 to +30.0‰; Veizer and Hoefs, 1976) and lesser than the sedimentary organic matter (+24.0 to +35.0‰; Liu and Liu, 1997 (Zheng and Chen, 2000) are lower than those of sedimentary organic matters, marine carbonate rocks, but are analogous to those of mantle or metamorphic fluids having documented values of +2 to + 25‰ (Hoefs, 2009). Inference can be made that the mantle and organic matters did not contribute a substantive amount of carbon to the hydrothermal fluids and suggested that the carbon in the fluids was probably injected by the carbonate host rocks of the Carboniferous Baizuo Formation (Han et al, 2007;Zhang et al, 2017). Also, based on (Fig.…”
Section: Insights From C-o Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas phase components contain CO 2 + CH 4 + N 2 (Han et al, 2007a;Han et al, 2016;Zhang et al, 2017a). The results show that gas-liquid differentiation occurs during the oreforming process.…”
Section: Typical Sygt Deposit Characteristicsmentioning
confidence: 88%
“…Hydrogen and oxygen isotopes can effectively identify the ore-forming fluid source (Huang et al, 2019b). Zhang et al (2017a) identified the two different metallogenic fluids by C-H-O isotope: a high temperature, low salinity, and acidic Fluid A, which originates from deep-seated fluids and is enriched in lighter C -O-H isotopes (−3‰ < δ 13 C ‰ < −4‰; 10‰ < δ 18 O‰ <17‰; −92‰ < δD‰ < −50‰), and a low temperature, high salinity Fluid B, which is a subsurface brine formed by atmospheric precipitation. Fluid B is characterized by heavier C-O-H isotopic compositions (−2‰ < δ 13 C‰ < 1‰; 2‰ < δ 18 O‰ < 24‰; −66‰ < δD‰ < −43‰) than Fluid A and cycles continuously within the strata.…”
Section: Isotope Geochemistrymentioning
confidence: 99%